How innovation can be defined, evaluated and rewarded in health technology assessment - Juan Carlos Rejon-Parrilla; Jaime Espin; David Epstein (Health Economics Review, 2022)
Background: What constitutes innovation in health technologies can be defined and measured in a number of ways and it has been widely researched and published about. However, while many countries mention it as a criterion for pricing or reimbursement of health technologies, countries differ widely in how they define and operationalise it. Methods: We performed a literature review, using a snowballing search. In this paper, we explore how innovation has been defined in the literature in relation to health technology assessment. We also describe how a selection of countries (England, France, Italy, Spain and Japan) take account of innovation in their health technology assessment frameworks and explore the key methodologies that can capture it as a dimension of value in a new health technology. We propose a way of coming to, and incorporating into health technology assessment systems, a definition of innovation for health technologies that is independent of other dimensions of value that they already account for in their systems, such as clinical benefit. We use Spain as an illustrative example of how innovation might be operationalised as a criterion for decision making in health technology assessment. Results: The countries analysed here can be divided into 2 groups with respect to how they define innovation. France, Japan and Italy use features such as severity, unmet need and therapeutic added value as indicators of the degree of innovation of a health technology, while England, Spain consider the degree of innovation as a separate and additional criterion from others. In the case of Spain, a notion of innovation might be constructed around concepts of "step-change", "convenience", "strength of evidence base" and "impact on future research & development". Conclusions: If innovation is to be used as operational criteria for adoption, pricing and reimbursement of health technologies, the concept must be clearly defined, and it ought to be independent from other value dimensions already captured in their health technology assessment systems.
Keywords: 330; Innovation; Health technology assessment; Value; Health policy